Okul Yöneticilerinin Yeşil Örgütsel Davranışlarını Belirlemeye Yönelik Bir Araştırma - Sönmez, Ramazan Vedat (Muş Alparslan Üniversitesi, 2020)
There is an increase in the use of natural resources in the industrial revolution co-production process-es. In parallel with this increase, it has reached important dimensions in the wastes released by the organizations to the natural environment. Natural resources cannot renew itself at the rate of con-sumption. Therefore, the transfer and sustainability of resources from one generation to the next, environmental pollution has recently occupied the agenda of public and private sector managers.The use of natural resources and damage to the environment also affect organizational activities, and it is stated all the employees in an organization are required to take this point into consideration. The purpose of this study; to determine the green organizational behavior of the administrators operating in educational enterprises, in other words, to measure the environmental sensitivity, environmental participation, economic sensitivity, green purchasing and technological sensitivity levels of school administrators, to determine their attitudes on this subject, to contribute to the relevant literature, creating a discussion environment. The research was carried out for administrators working in public schools in Cizre district of Şırnak province and survey technique was used in data collection. As a result of the research; It was found that the participants'environmental sensitivity, environmental participation, economic sensitivity, green purchasing and technological sensitivity levels were quite high.

nayi devrimi birlikte üretim süreçlerinde doğal kaynak kullanımında bir artış yaşanmaktadır. Bu artışa paralel olarak örgütler tarafından doğal çevreye salınan atıklarda önemli boyutlara ulaşmış bulunmak-tadır. Doğal kaynaklar tüketildiği hızda kendini yenileyememektedir. Bu nedenle kaynakların bir nesilden diğerine aktarımı ve sürdürülebilirliği, çevre kirliliği son dönemlerde kamu ve özel sektör yöneticilerinin gündemini işgal etmektedir. Doğal kaynakların kullanımı ve çevreye verilen zarar örgütsel faaliyetler tarafından da etkilenmekte, örgütsel çatı altında çalışan tüm iş görenlerin dikkat etmeleri gereken bir husus olduğu ifade edilebilmektedir. Bu çalışmanın amacı; eğitim işletmelerinde faaliyette bulunan yöneticilerin yeşil örgütsel davranışlarını belirlemek, bir başka ifade ile okul yöne-ticilerinin çevresel duyarlılık, çevresel katılım, ekonomik duyarlılık, yeşil satın alma ve teknolojik duyarlılık düzeylerini ölçmek, bu konudaki tutumlarını belirlemek, ilgili literatüre katkı sunmak, konu ile ilgili yeni bir tartışma ortamı yaratabilmektir. Araştırma Şırnak ili, Cizre ilçesinde resmi okullarda görev yapan yöneticilere yönelik yapılmış olup veri toplama işleminde anket tekniği kullanılmıştır. Araştırma sonucunda; katılımcıların çevresel duyarlılık, çevresel katılım, ekonomik duyarlılık, yeşil satın alma ve teknolojik duyarlılık düzeylerinin oldukça yüksek seviyede olduğu bulunmuştur.
A Research on Determining Green Organizational Behaviors of School Administrators
anemon
Keywords: Natural Environment; Environmental problems; Green Organizational Behavior; Administration; School Management; Doğal çevre; Çevre sorunları; Yeşil Örgütsel Davranış; Yönetim; Okul Yönetimi